PENGEMBANGAN MEDIA PEMBELAJARAN MAJALAH PINTAR EDUKATIF IPS PADA PESERTA DIDIK KELAS IV - St. Erfi Yulvira; Indhira Asih Vivi Y; Rina Yuliana; Windar Yanti; M. Taufik; Indhira Asih Viviani Yandari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The development research is conducted to find out how the process of developing smart educational magazine media, how the feasibility of smart educational magazine media,and how the response of students using educative smart magazines for grade IV students of MI Al-Khairiyah Pipitan are within this article. The research method used a research and developmental (R&D) research with a 3D development model (Three-D), which consists of three stages, define, design, and development. To test the feasibility of this learning media, it was tested by expert validations. The validation was carried out by experts in instrument validation, media, material, and language. The research subject involved 20 students of class IV at MI Al-Khairiyah. Based on the result, this smart educational magazine media achieved an average score of 92% based on expert validation so it was categorized as the "very feasible" category and an average score of 90% based on student responses, which was classified as the "very feasible" category. Clearly, this educational smart magazine learning media is feasible to use.